The political philosophy of Jean-Jacques Rousseau: The impossibility of reason - Qvortrup, Mads (Manchester University Press, 2003)
This exciting new book presents the first overview of Jean Jacques Rousseau's work from a political science perspective. Was Rousseau - the great theorist of the French Revolution - really a conservative? This original study argues that the author of The Social Contract was a constitutionalist much closer to Madison, Montesquieu and Locke than to revolutionaries. Outlining his profound opposition to Godless materialism and revolutionary change, this book finds parallels between Rousseau and Burke, as well as showing that Rousseau developed the first modern theory of nationalism. The book presents an integrated political analysis of Rousseau's educational, ethical, religious and political writings, and will be essential reading for students of politics, philosophy and the history of ideas.